Attosecond control of orbital parity mix interferences and the relative phase of even and odd harmonics in an attosecond pulse train - Laurent, Guillaume; Cao, Wei; Li, H.; Wang, Zhenhua; Ben-Itzhak, Itzik; Cocke, Charles L. (My University, 2012)
We experimentally demonstrate that atomic orbital parity mix interferences can be temporally controlled on an attosecond time scale. Electron wave packets are formed by ionizing argon gas with a comb of odd and even high-order harmonics, in the presence of a weak infrared field. Consequently, a mix of energy-degenerate even and odd parity states is fed in the continuum by one- and two-photon transitions. These interfere, leading to an asymmetric electron emission along the polarization vector. The direction of the emission can be controlled by varying the time delay between the comb and infrared field pulses. We show that such asymmetric emission provides information on the relative phase of consecutive odd and even order harmonics in the attosecond pulse train.
Keywords: Atomic orbital parity mix interferences; Attosecond pulse train; Laser physics; Electronic dynamics